1975
DOI: 10.1172/jci108243
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral metabolism of insulin, proinsulin, and C-peptide in the pregnant rat.

Abstract: AB ST R A CT To clarify alterations in carbohydrate metabolismI whllich occuir in pregnancy, metabolic clearance rates of insulin, proinsulin, and C-peptide were measured by the constant infusion technique in term-pregnant rats and in virgin littermates. In addition, placental permeability to these peptides was evaluated by simultaneous determination of their conicentration in fetal blood, amniiotic fluid, and maternal arterial blood, and the renal extraction and excretion of insulin and C-peptide were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…This also applies to insulin-treated diabetics in whom exogenous insulin as well as endogenous insulin antibodies interfere with the measurement of endogenous insulin (13). In animals (15)(16)(17) as well as in humans (18,19), the turn-over of C-peptide is slower than that of insulin. However, detailed studies concerning the kinetics of C-peptide turnover have not been carried out in normal man.…”
Section: Introductionmentioning
confidence: 99%
“…This also applies to insulin-treated diabetics in whom exogenous insulin as well as endogenous insulin antibodies interfere with the measurement of endogenous insulin (13). In animals (15)(16)(17) as well as in humans (18,19), the turn-over of C-peptide is slower than that of insulin. However, detailed studies concerning the kinetics of C-peptide turnover have not been carried out in normal man.…”
Section: Introductionmentioning
confidence: 99%
“…The placenta is impermeable to polypeptides and protein hormones. 32,33 Thus, an increase in fetal hormones was independent of the maternal side. New findings of this study include the following: first, the substrate angiotensinogen in the fetal liver, the main source in peripheral systems for the precursor of Ang II, was significantly increased by maternal dehydration; second, an increase in fetal plasma Ang I indicated that either production of angiotensinogen or activity of a key enzyme renin in the fetus was enhanced; and third, the major bioactive peptide of the RAS-Ang II in the fetal circulation was markedly increased following maternal water deprivation.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, it has been shown that there is negligible hepatic extraction of C-peptide in rats (Stoll et al 1970), normal dogs (Polonsky et al 1983) and dogs given oral glucose . Furthermore, the clearance of C-peptide has been found to be constant under a wide range of physiological conditions and at varying concentrations of plasma C-peptide in rats (Katz et al 1975), dogs (Polonsky et al 1983; and humans (Faber et al 1979).…”
Section: Discussionmentioning
confidence: 99%